What is a parasport coach's role during athlete classification? Exploring how parasport coaches learn about classification and their role within this process - Birchall, I.; Lawson, J. A.; Williams, T. L.; Latimer-Cheung, A. E. (International Sport Coaching Journal, 2024)
Undergoing classification can be a difficult experience for athletes with disabilities, yet coaches may support athletes during this event. However, research has yet to examine either coaches` roles during classification or how coaches learn to navigate this unique aspect of parasport. We purposed to explore parasport coaches` roles during classification as well as the ways in which coaches learn about classification. Twelve Canadian high-performance coaches representing eight parasports participated in semistructured interviews. Inductive reflexive thematic analysis of the transcripts was conducted. Results show coaches view their role as intuitive and centered on preparing the athlete, ensuring fairness, and reframing classification outcomes. The ways coaches learned about classification varied, but coaches agreed there is a general lack of structured resources available to coaches interested in learning about classification. In addition to learning about classification, coaches valued understanding the athlete and their impairment to effectively fulfill their coaching roles.